Validation and development of freshwater invertebrate metabarcoding COI primers for Environmental Impact Assessment - Elbrecht, Vasco; Leese, Florian (PeerJ Preprints, 2016)
To assess and manage human impacts on freshwater ecosystems is a central challenge in the present era of biodiversity loss. Macroinvertebrates are an ideal group for Environmental Impacts Assessment (EIA). However, generating accurate macroinvertebrate inventories is difficult and error-prone based on larval morphology. Here, DNA metabarcoding provides new opportunities. Its potential to accurately identify bulk invertebrates on species level has been demonstrated in several case studies. However, DNA based identification is often limited by primer bias, potentially leading to taxa in the sample remaining undetected. Thus, the success of DNA metabarcoding as an emerging technique for EIA critically relies on carefully evaluated primers. We used the R package PrimerMiner to obtain and process cytochrome c oxidase I (COI) sequence data for the 15 globally most relevant freshwater invertebrate groups in EIAs. Using these sequence alignments, we developed four primers combinations optimized for freshwater macrozoobenthos. All primers were evaluated by sequencing ten mock community samples each consisting of 52 freshwater invertebrate taxa. Additionally popular metabarcoding primers from the literature and the here developed primers were tested in silico against the 15 relevant invertebrate groups. The developed primers varied in amplification efficiency and the amount of detected taxa, yet all retrieved more taxa than standard ‘Folmer’ barcoding primers. Two new primer combinations showed more consistent amplification than a previously tested ribosomal marker (16S) and detected all 42 insect taxa present in the mock community samples. In silico evaluation revealed critical design flaws in some commonly used primers from the literature. We demonstrate a reliable strategy to develop optimized primers using the tool PrimerMiner. The developed primers detected almost all taxa present in the mock samples, and we argue that high base degeneracy is necessary to decrease primer bias as confirmed by experimental results and in silico primer evaluation. We further demonstrate that not all primers currently used in metabarcoding studies are likely not suitable for amplification of insect and freshwater taxa. Thus careful primer evaluation and more region / ecosystem specific primers might be needed, before DNA metabarcoding can be used for routine EIA of freshwater ecosystems.
Keywords: DNA Barcoding; primer evaluation; in silico PCR; ecosystem assessment; primer bias; Primer development